Visual adaptation provides objective electrophysiological evidence of facial identity discrimination. (July 2016) - Retter, Talia L.; Rossion, Bruno
Abstract: Discrimination of facial identities is a fundamental function of the human brain that is challenging to examine with macroscopic measurements of neural activity, such as those obtained with functional magnetic resonance imaging (fMRI) and electroencephalography (EEG). Although visual adaptation or repetition suppression (RS) stimulation paradigms have been successfully implemented to this end with such recording techniques, objective evidence of an identity-specific discrimination response due to adaptation at the level of the visual representation is lacking. Here, we addressed this issue with fast periodic visual stimulation (FPVS) and EEG recording combined with a symmetry/asymmetry adaptation paradigm. Adaptation to one facial identity is induced through repeated presentation of that identity at a rate of 6 images per second (6 Hz) over 10 sec. Subsequently, this identity is presented in alternation with another facial identity (i.e., its anti-face, both faces being equidistant from an average face), producing an identity repetition rate of 3 Hz over a 20 sec testing sequence. A clear EEG response at 3 Hz is observed over the right occipito-temporal (ROT) cortex, indexing discrimination between the two facial identities in the absence of an explicit behavioral discrimination measure. This face identity discrimination occurs immediately after adaptation and disappears rapidly within 20 sec. Importantly, this 3 Hz response is not observed in a control condition without the single-identity 10 sec adaptation period. These results indicate that visual adaptation to a given facial identity produces an objective (i.e., at a pre-defined stimulation frequency) electrophysiological index of visual discrimination between that identity and another, and provides a unique behavior-free quantification of the effect of visual adaptation.